Jack force effect to tunnel stability - Osama Mohamed El Sayed Mohamed Abdelaal, 1995- author 640855 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2021)
Thesis (Sarjana Falsafah, Bidang Penyelidikan : Geoteknik)